Quantifying Older Adults’ Spatial Perceptions of Outdoor Activity Areas for Embedded Retirement Facilities - Guannan Fu; Yinan Gai; Liqun Xiang; Lin Lin (Buildings)
Outdoor activity areas for embedded retirement facilities (ERFs) are essential for providing older adults with access to outdoor environments within communities. However, there is limited evidence on how these areas influence older adults’ spatial perceptions. This study investigated the impact of ERFs’ spatial characteristics on older adults’ physiological and psychological perceptions. Three kinds of outdoor activity areas in a coastal city in eastern China were investigated, and older adults’ physiological data were collected through real environments from wearable sensors. Their subjective perception data were collected through subjective satisfaction questionnaires. By combining them, the authors identified correlations between older adults’ spatial perceptions and the characteristics of outdoor activity areas, quantifying the impact of various spatial features on their satisfaction. The results showed that areas with high subjective satisfaction were linked to strong emotional arousal and increased visual comfort. Spaces with favourable sky view factors and spatial openness significantly enhanced spatial perception satisfaction. Key design elements can shape older adults’ spatial perceptions. This study highlights the positive relationship between outdoor activity areas for ERFs and older adults’ spatial experiences, offering insights for age-friendly renovations and site selection to create supportive environments for ageing populations.